2006
DOI: 10.1016/j.jacc.2005.11.030
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Strongly Reflects Diastolic Wall Stress in Patients With Chronic Heart Failure

Abstract: The present study shows that plasma BNP levels reflect left ventricular EDWS more than any other parameter previously reported, not only in patients with SHF, but also in patients with DHF. The relationship of left ventricular EDWS to plasma BNP may provide a better fundamental understanding of the interindividual heterogeneity in BNP levels and their clinical utility in the diagnosis and management of HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
327
4
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(355 citation statements)
references
References 26 publications
13
327
4
11
Order By: Relevance
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…These results are consistent with the known pathophysiology of HF-PLEF where a variety of clinical conditions can ultimately lead to an increased left ventricular end diastolic wall stress. Iwanaga et al have demonstrated that BNP levels correlate very closely with left ventricular end diastolic wall stress in the setting of HF-PLEF (r 2 = 0.887) making it a good surrogate marker of worsening DD [25]. Moreover, BNP was shown to strongly correlate with pulsed wave Doppler and tissue Doppler parameters in patients with HF-PLEF [26].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,16 It has been suggested that LV end-diastolic wall stress is the most important hemodynamic parameter regulating the levels of circulating BNP. 12,17 Of note, circulating BNP reflects the balance between BNP release and elimination. In contrast, our data suggest that LVESWS is the key loading parameter for ⌬ A-CS BNP, that is, cardiac BNP release, indicating that LV geometry and afterload rather than filling pressures are the most important mechanical determinants of cardiac BNP release.…”
Section: Discussionmentioning
confidence: 99%
“…LV end-diastolic wall stress and LV end-systolic wall stress (LVESWS) were calculated using the following formula: wall stressϭ0.334*LV pressure*LV internal diameter/(posterior wall thickness*[1ϩposterior wall thickness/LV internal diameter]), where LV internal diameter and posterior wall thickness at end diastole or end systole were used. 12 PCWP was used as a surrogate for LV end-diastolic pressure, and systolic arterial pressure was used as a substitute for LV end-systolic pressure.…”
Section: Cardiac Catheterizationmentioning
confidence: 99%